Engineered living conductive biofilms as functional materials. (June 2019) - Bird, Lina J.; Onderko, Elizabeth L.; Phillips, Daniel A.; Mickol, Rebecca L.; Malanoski, Anthony P.; Yates, Matthew D.; Eddie, Brian J.; Glaven, Sarah M.
Abstract: Abstract : Natural living conductive biofilms transport electrons between electrodes and cells, as well as among cells fixed within the film, catalyzing an array of reactions from acetate oxidation to CO2 reduction. Synthetic biology offers tools to modify or improve electron transport through biofilms, creating a new class of engineered living conductive materials. Engineered living conductive materials could be used in a range of applications for which traditional conducting polymers are not appropriate, including improved catalytic coatings for microbial fuel-cell electrodes, self-powered sensors for austere environments, and next-generation living components of bioelectronic devices that interact with the human microbiome.